2014
DOI: 10.1088/1748-9326/9/3/034012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of offshore wind farms on marine wildlife—a generalized impact assessment

Abstract: Marine management plans over the world express high expectations to the development of offshore wind energy. This would obviously contribute to renewable energy production, but potential conflicts with other usages of the marine landscape, as well as conservation interests, are evident. The present study synthesizes the current state of understanding on the effects of offshore wind farms on marine wildlife, in order to identify general versus local conclusions in published studies. The results were translated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
107
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 78 publications
(36 reference statements)
2
107
0
1
Order By: Relevance
“…Additionally, effects should be evaluated across multiple spatial and temporal scales to determine population-level effects on resident fish and macro-invertebrates (Bergstrom et al, 2014;Lindeboom et al, 2015). Many species use large areas during their life span (e.g., egg, larval, juvenile, adult stages), often make long-distance seasonal migrations (Secor, 2015), and therefore small-scale effects (on the scale of individual WEAs) may have additive effects (Bergstrom et al, 2014;Dai et al, 2015) on populations of commercially and ecologically important fish and macro-invertebrates.…”
Section: Cca1 (182%)mentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, effects should be evaluated across multiple spatial and temporal scales to determine population-level effects on resident fish and macro-invertebrates (Bergstrom et al, 2014;Lindeboom et al, 2015). Many species use large areas during their life span (e.g., egg, larval, juvenile, adult stages), often make long-distance seasonal migrations (Secor, 2015), and therefore small-scale effects (on the scale of individual WEAs) may have additive effects (Bergstrom et al, 2014;Dai et al, 2015) on populations of commercially and ecologically important fish and macro-invertebrates.…”
Section: Cca1 (182%)mentioning
confidence: 99%
“…Assessment of the impacts of the location, construction, and energy production of offshore wind farms on fish and macro-invertebrates on the northeast U.S. shelf is in the early stages. However, European countries have been conducting environmental assessments since the early 1990s that have resulted in review articles on the general impacts of, and long-term research needs for, offshore wind farms (Wilson et al, 2010;Lindeboom et al, 2011;Bailey et al, 2014;Bergstrom et al, 2014;Dai et al, 2015;Lindeboom et al, 2015). The reviews have generally concluded there are potentially minor to moderate effects on fish and macro-invertebrate communities.…”
mentioning
confidence: 99%
See 3 more Smart Citations